Communication accommodation amongst Congolese Facebook users - Tsoumou, Jean Mathieu (Huarte de San Juan. Filología y Didáctica de la Lengua, 2021)
Facebook is one of the top social media in use worldwide at present. With millions of people around the globe frequently communicating on the social media, investigating users’ interactions and their behaviour on Facebook is a breakthrough in an attempt to gain an understanding of how people behave beyond their traditional face-to-face space. The present study intends to examine patterns of communication accommodation in Facebook interaction amongst Congolese users. Applying communication accommodation theory to analyse a dataset of 262 Facebook updates, the study reveals that, though there is no one-on-one correlation between the incidences of Codeswitching (henceforth CS) in Facebook updates and comments, the two main concepts of communication accommodation theory – namely convergence and divergence – are observed as the main communicative strategies used by Congolese Facebook users.